2022
DOI: 10.3389/fpubh.2022.912077
|View full text |Cite
|
Sign up to set email alerts
|

Food handler's level of COVID-19 prevention practice and preparedness of food and drinking establishments to combat the pandemic in Eastern Ethiopia

Abstract: BackgroundFood and drinking establishments are potential hotspots for the spread of coronavirus. Food handler's have a higher risk of contracting the disease and transmitting it to others. The aim of this study was to assess the food handler's level of preventive practices toward COVID-19 and the preparedness of food and drinking establishments to tackle the pandemic in Eastern Ethiopia.MethodsThe cross-sectional study design was conducted from September 1 to 30, 2020. A stratified sampling technique was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…Two possible reasons for the inconsistency are that the knowledge measurement items differ, and the other is that Ferreira et al ( 13 ) study only targeted food workers in public school food services, who, since food safety in schools is of great concern, may have more training. Moreover, knowledge was also identified as a significant promoter of worker adherence to hygiene practices, which is consistent with the outcome of many previous studies, such as Habte et al ( 5 ), Akabanda et al ( 10 ), Sani and Siow ( 12 ). It should be noted, however, that while knowledge has a significant positive effect, the effect magnitude is not strong that is significantly lower than the self-efficacy and risk perception ones in the cognitive dimension, implying that the knowledge–behavior gap still remains among food workers ( 33 ).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Two possible reasons for the inconsistency are that the knowledge measurement items differ, and the other is that Ferreira et al ( 13 ) study only targeted food workers in public school food services, who, since food safety in schools is of great concern, may have more training. Moreover, knowledge was also identified as a significant promoter of worker adherence to hygiene practices, which is consistent with the outcome of many previous studies, such as Habte et al ( 5 ), Akabanda et al ( 10 ), Sani and Siow ( 12 ). It should be noted, however, that while knowledge has a significant positive effect, the effect magnitude is not strong that is significantly lower than the self-efficacy and risk perception ones in the cognitive dimension, implying that the knowledge–behavior gap still remains among food workers ( 33 ).…”
Section: Discussionsupporting
confidence: 89%
“…Our survey revealed that near half of the knowledge of hygiene practices is poorly understood by food workers, which implies that the knowledge of food handling possessed by professionals who handle food is significantly inadequate. This result is similar to the results of Habte et al ( 5 ) survey on food handlers’ knowledge in Ethiopia (mean correct rate = 58.4%) and Olaimat et al ( 32 ) survey on food handlers’ knowledge in Jordan, but lower than the results of Ferreira et al ( 13 ) survey on food workers in Brazil (mean correct rate = 72.2%). Two possible reasons for the inconsistency are that the knowledge measurement items differ, and the other is that Ferreira et al ( 13 ) study only targeted food workers in public school food services, who, since food safety in schools is of great concern, may have more training.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations